Development of a Screening Tool for Common Mental Disorders Among General Hospital Inpatients in China - Yuan, Shuai; Shen, Yizhong; Liu, Jingwen; Chen, Zilin; Zheng, Lijiao; Chen, Lihao; Chen, Hanwei; Feng, Huiqiang; He, Hongbo (Frontiers in Psychiatry, 2021)
Background: Depression and anxiety are common conditions among general hospital inpatients, but are believed to be under-recognized in China. Methods: A short, practical questionnaire termed the happiness index scale (HIS) was developed for screening co-morbid mental illnesses in non-psychiatric clinical settings. The HIS was completed by 1005 non-psychiatric inpatients in a general hospital in China. The reliability and validity of the HIS were then assessed. Results: The HIS comprised eight items which loaded onto four dimensions: (a) sleep quality; (b) suicidal tendency; (c) depression; and (d) anxiety. These dimensions explained 84.2% of the total variance. Confirmatory factor analysis showed reasonably good fit of the four-factor model (χ2/df=1.27, p < 0.001, goodness-of-fit index = 0.95, comparative fit index = 0.99, root-mean-square error of approximation = 0.008). The correlation coefficients between each item and the corresponding factor were all > 0.5. Cronbach’s α of the entire scale was 0.83, indicating good internal consistency. The area under the ROC curve was 0.95 compared with the original 31-item scale. Using the optimal cut-off score of HIS (mild happiness), the sensitivity and specificity were 0.933 and 0.882, respectively. Conclusions: The new HIS scale is a practical screening tool composed of eight items covering the four most common and important dimensions of mental illness. The HIS exhibited good reliability and specificity. The HIS is potentially suitable for large-scale screening in busy non-psychiatric clinical settings in China. Further verification using larger samples is warranted.